Laboratory-Scale Implementation of Standardized Reconstituted Geothermal Water for Electrochemical Investigations of Carbon Steel Corrosion - Stephanie Betelu; Chahinez Helali; Ioannis Ignatiadis (Metals)
Currently, the demand for heat production by geothermal energy is increasingly strong amid the controversy surrounding non-renewable forms of energy. In France, the Dogger aquifer in the Paris Basin (DAPB) produces saline geothermal waters (GWs) that are hot (70–85 °C), anaerobic, and slightly acidic (pH 6.1–6.4), and are characterized mainly by the presence of Cl−, SO42−, CO2/HCO3−, and H2S/HS. These GWs are corrosive, while the well casings used are carbon steel. GWs have been continuously treated since the 1990s by corrosion inhibitors at the bottom of production wells to reduce water–steel interactions and scaling issues. Electrochemical experiments to optimize inhibitors were carried out on site, protected from the ambient atmosphere, with actual geothermal water, using water tapping at the wellhead. Currently, carbon steel corrosion/scaling, corrosion inhibition phenomenology, and kinetics evaluation remain important challenges. These issues are, of course, linked to the durability of installations. The novelty of our work consists of our validation of a modus operandi that properly reproduces, at the laboratory scale, operating conditions similar to those encountered on the types of geothermal installations. Particular attention was paid to characterizing waters and gases from 13 production wellheads that were modelled with PhreeqC® Version 3 hydrogeochemical software and the Thermoddem thermodynamic database for implementing standardized reconstituted geothermal water (SRGW), a well-balanced water representative of the major elements and dissolved gases of actual DAPB geothermal waters. The developed electrochemical setup enabled us to analyze corrosion mechanisms such as those observed on site and to investigate corrosion inhibition using petrosourced and biosourced inhibitors. The modus operandi constitutes a reference for further investigations, at the laboratory scale, of corrosion inhibition. These investigations may include screening and optimizing the formulas of petrosourced and biosourced inhibitors for use in DAPB waters.